IDENTITAS SOSIAL DAN KURIKULUM INKLUSIF: Sebuah Investigasi di Sekolah Dasar Negeri 1, 2 dan 6 di Kota Palu Tahun 2023 - Taufik, Taufik (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2024)
This research aims to describe the implementation of an inclusive curriculum in shaping social identity. This is crucial in communities with diverse ethnicities, religions, traditions, cultures, and more, enhancing references for educational strategies, particularly in elementary schools in Palu. The study employs a qualitative method with an ethnographic approach, utilizing both primary and secondary data sources. Data collection techniques include document analysis, observation, and in-depth interviews. After data gathering, document analysis focuses on curriculum documents and others. Data analysis reveals that implementing an inclusive curriculum significantly strengthens students' social identities through increased social interactions and appreciation of local cultural diversity, exemplified by the concept of